Cinema transnacional e tendências estéticas nas revistas brasileiras Fon-Fon e Cinearte : (1927 a 1932) - Haussen, Luciana Fagundes (2015)
This research proposes the analysis of the Brazilian magazines Fon-Fon and Cinearte within the time frame from 1927 to 1932. During the period, we sought to identify the presence of a transnational cinema, traces of an incipient globalized culture and aesthetic elements linked to Art Deco . The study has a qualitative character on film, culture and historical context, in a Brazil with an incipient cinema and communications landscape also being consolidated. The six years proposed for analysis comprise a rich time of information about the settings of new markets, consumption habits, media and aesthetic trends. And the research seeks to establish a dialogue between existing content on Fon-Fon and Cinearte, and these with the elected bibliography, at an intersection with the Brazilian historical context, to propose a look at the transnational cinema, globalized culture and aesthetic trends presented in Brazil during the period, within the universe of the two magazines. The theoretical framework highlights the works of Tim Bergfelder on transnational cinema; Lucy Fischer, for the approach to the Art Deco and aesthetic trends; the research of Joseph Garncaz, Chris Wahl, Joel Westerdale e Christian Rogowski, for new perspectives on the study of the Weimar cinema; and the works of Renato Ortiz to treat globalization of culture.